'Tamper (the play in it)'. (4th July 2018) - Williams, David
Abstract : This essay is about play, games, sport and education, and the 'give' in the apparent fixity of some of their rules and structures. With reference to cricket, and in particular the structure and dynamic possibilities of the ball in the act of bowling, it reflects on cheating and/as performance, material transformation over time, unpredictability, turbulence and swing. It also explores the histories and contested practices of ball tampering, an array of techniques for illegitimately gaining advantage by accelerating the deterioration of the condition of the ball. Tampering involves deception, simulation and disguise, discreetly and necessarily concealed within a performed and illusory pretense of playing by the rules and 'playing the game', while incrementally introducing a kind of sinister underhand deviation in the predictable and orderly, a swerve of difference in repetition. The essay includes detailed instruction on tampering techniques and a suggested toolkit for tamperers.